Pengaruh penggunaan Media Pembelajaran Gimkit terhadap Kemampuan Berpikir Historis Peserta Didik Kelas XI SMK Ibu Kartini Semarang - Naufal Maulana Fatah; Hany Nurpratiwi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of the use of game-based Gimkit learning media on the historical thinking skills of eleventh-grade students. The background of this study is based on the low historical thinking skills of students who still tend to be oriented towards memorization and lack of active student involvement in analyzing historical events. The study used a quantitative approach with a quasi-experimental method through a nonequivalent control group design. The research sample consisted of 43 students divided into an experimental class of 21 students and a control class of 22 students. The experimental class received learning using game-based Gimkit media, while the control class received learning assisted by PowerPoint media. Data collection techniques were carried out through historical thinking ability tests using pretest and posttest instruments. Data analysis was carried out using descriptive statistical tests, N-Gain calculations, and Independent Sample t-tests with the help of SPSS version 21. The results showed that the average N-Gain of the experimental class was 0.7115 in the high category, while the control class obtained an average of 0.3892 in the medium category. The results of the hypothesis test showed a calculated t-value of 20.518 > t-table 2.019 with a significance value of 0.000 < 0.05, thus the alternative hypothesis was accepted. These findings indicate that the use of game-based Gimkit learning media has a positive and significant impact on improving students' historical thinking skills. Thus, Gimkit can be used as an alternative, innovative history learning medium to improve students' historical thinking skills.